School-Age Child Mortality: The Impact of Women's Autonomy and Household Characteristics - M. Dharma Nauval; Asnawi Abdullah; Nopa Arlianti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Child mortality is a crucial indicator for achieving the Sustainable Development Goals (SDGs) for 2030 and the National Medium-Term Development Plan (RPJMN) 2020-2024 in healthcare. It reflects advancements in health and human capital, with SDG targets aiming for a neonatal mortality rate of 12 per 1,000 live births by 2030, and RPJMN targeting a child mortality rate of 16 per 1,000 live births by 2024. School-age (5-9 years) and adolescent (10-18 years) stages are critical for education and character development, where parental roles, especially women's autonomy in decision-making regarding family and education, are essential for ensuring health and well-being. Objective: The aim of this study is to examine the impact of women's autonomy, household wealth, residential area, parental occupations, and age at marriage on school-age child mortality. Method: This study uses a quantitative cross-sectional design with secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS). The sample includes 37,246 mothers of children aged 6 to 18 years. Inclusion criteria were mothers whose last child died between ages 6 and 18, who were married and living with their spouse, and who knew their age at first marriage. Exclusion criteria were women under 15 or over 49 years, deaths outside the specified age range, women unaware of their marriage age, and those who were divorced or widowed. Data were analyzed using bivariate logistic regression and multivariate stepwise regression to evaluate the effects of women's autonomy, household wealth, residential area, parental occupations, and age at marriage on school-age child mortality. Result: The results of the bivariate analysis indicate significant associations between women's autonomy (P=0.022; OR=0.92), age at first marriage (P=0.0001; OR=1.8), father’s occupation (P=0.0001; OR=1.4), and residential area (P=0.0001; OR=1.5) with school-age child mortality. No significant relationship was found between maternal occupation (P=0.122; OR=0.95) and household wealth status (P=0.459; OR=0.98) with school-age child mortality. The multivariate stepwise analysis confirmed that women's autonomy, age at first marriage, father’s occupation, and residential area remained significant factors. Conclusion: The study underscores the importance of empowering women, raising awareness about early marriage, and implementing economic interventions to reduce school-age child mortality. Additionally, it recommends further research on women's autonomy, including supportive and obstructive factors, to deepen understanding in this area. Such research can aid in developing more holistic policies and interventions.